Estimates of methane emissions from the Southern Ocean from quasi-continuous underway measurements of the partial pressure of methane in surface seawater during the 2012/13 austral summer. Issue 1 (1st January 2018) - Bui, Oanh Thi Ngoc; Kameyama, Sohiko; Yoshikawa-Inoue, Hisayuki; Ishii, Masao; Sasano, Daisuke; Uchida, Hiroshi; Tsunogai, Urumu
Abstract: We used a new underway measurement system to investigate the partial pressure of methane (CH4 ) in surface seawater and overlying air in the Southern Ocean from late November 2012 to mid-February 2013. The underway system consisted of a cavity ring-down spectroscopy analyser and a shower-head type equilibrator. The monthly mean atmospheric CH4 mixing ratios obtained agreed well (within 5 ppb) with those recorded at onshore baseline stations. CH4 saturation ratios ( SR, %), defined as CH4 concentration in seawater divided by CH4 concentration equilibrated with atmospheric CH4, varied between 85 and 185%; most of the ratios we calculated indicated supersaturation, except for those from south of the Southern limit of Upper Circumpolar Deep Water. SR was higher at the lower latitudes, including coastal areas north of the Sub-Antarctic Front, but decreased gradually and monotonously between the Sub-Antarctic Front and the Upper Circumpolar Deep Water. At high latitudes south of the Polar Front, SR decreased to below 100% due to the effects of upwelling and vertical mixing. We found a strong linear correlation between SR and apparent oxygen utilisation (AOU) south of the Polar Front. Observed SR decreased with increasing AOU and reached 85% at high AOU (41 µmol kg −1 ) and low temperature (–1.8 °C). On the basis of the linear relationship between SR and AOU, we evaluated the climatological sea–air flux of CH4 from December to February for the entire Southern Ocean south of 50°S: Sea–air CH4 emission was estimated to be 0.027 Tg yr −1 in December, 0.04 Tg yr −1 in January, and 0.019 Tg yr −1 in February.